Centrality of space in the strategic construal of up in English particle verbs - Geld, Renata; Letica Krevelj, Stela (2011)
The paper explores the strategic construal of up in English particle verbs. It focuses on the role of topology (spatial relations) in L2 processing by investigating strategic thinking about linguistic meaning, and the process of dynamic and subjective construction of meaning pertaining to the human ability to understand and portray the same situation in alternate ways (Langacker 1987). There were five fundamental hypotheses governing our research: 1)semantic determination will depend on the nature of verbs in composite wholes (semantically heavy vs. semantically light) ; 2)semantic determination will depend on the nature of particle in composite wholes (degree of informativeness of up) ; 3)semantic determination will depend on the participants’ L1 ; 4)semantic determination will depend on the participants’ language proficiency ; 5)construal of up will resemble the process of grammaticalization. The participant sample in our research consisted of 100 users of English as L2, more specifically, proficient English majors from Croatia and Mexico. The results suggest that the process of meaning construction depends on a number of factors: 1)degree of schematicity/specificity of components in PVs, 2)degree of their informativeness. But, in addition to the nature of the component structures, the construal of the composite whole in L2 is affected by the users’ L1, i.e., their cognitive strategies in dealing with PV constructions are related to structures they encounter and use in their L1. Metaphorically speaking, the semantic battle between the particle and the verb will depend on type of structures favoured in L1 (e.g., Spanish speakers are more likely to rely on verbs than on particles). Finally, the relationship between the two component structures will depend on the users’ language proficiency. For example, irrespective of the degree of schematicity of the verb, those L2 users who are more proficient are more likely to attend to both components in the process of strategic meaning construal.
ENG